Patient satisfaction of a home diagnostic imaging service: a cross sectional study - Lorenzi, Lorena Jorge; Costa, Giovana Fondato; Kort, Helianthe; Castro, Paula Costa (Estudos Interdisciplinares sobre o Envelhecimento, 2026)
The study aimed to assess patient satisfaction with the provision of a home diagnostic imaging service in Brazil. This observational, cross-sectional study combines quantitative and qualitative approaches. Data were analyzed from an online satisfaction survey conducted by a company specializing in home diagnostic imaging, primarily for older adults. Patient satisfaction responses from February 2022 to June 2023 were examined across six aspects: scheduling, response time, staff courtesy, attention and care, hygiene and attire, and overall satisfaction. Additionally, an open-ended question gathered patient comments. Descriptive analyses and Bardin’s content analysis were performed. A total of 1,045 consultations were identified, with all satisfaction metrics receiving an average score above 9.6. Most comments were positive, highlighting the care provided by professionals, particularly humanized care and professionalism during the service. However, some patients reported challenges, such as scheduling delays and difficulties responding to the survey. The high satisfaction with the service and patient perspectives underscore the importance of home diagnostic services in expanding access to healthcare and promoting health equity.